RELATIONSHIP BETWEEN THE PHYSICAL CONDITION OF THE HOUSE AND THE HABITS OF THE PATIENT WITH THE INCIDENCE OF ACUTE RESPIRATORY INFECTIONS (ISPA) - Th. Teddy Bambang Soedjadi (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Unhealthy housing conditions will have a negative impact on human health, one of the impacts is ISPA. From the results of the Stabat Health Center data, ISPA is included in the 10 biggest diseases. Based on 2019 data, there were 1572 cases, an increase in cases occurred in 2020 to 1692 cases with a total of 206 cases in Sidomulyo Village. As well as the physical condition of the existing houses in Sidomulyo, there are still those that do not meet the requirements of a healthy house. This research is an analytic survey by exploring the causes of a phenomenon to occur with a cross sectional study design. The total population is 1.346 heads of families with a sample of 93 respondents. From the results of the study, it was found that there was a significant relationship between bedroom occupancy density and ISPA with a p value of 0.03, a significant relationship between ventilation and ISPA with a p value of 0.03, a significant relationship between smoking habits and ISPA with a p value of 0.011. there is a significant relationship between the habit of opening windows and ISPA with a p value of 0.01.